Studi komparasi kualitas pelayanan pada lembaga keuangan mikro syariah di Trenggalek Jawa Timur - Vika Mei Pratiwi; Dede Nurohman (LPMP Imperium, 2022)
Service quality is an advantage factor of institutions engaged in services. Each financial institution has different services from the others based on their respective characteristics. Service quality is created to meet all the needs and desires of members in accordance with their expectations. The research aims to find the ideal service quality that can be applied to Islamic microfinance institutions through a comparative study between Islamic microfinance institutions in Trenggalek. The approach used is a qualitative method with data collection techniques through observation, interviews, and documentation. This research was conducted by interviewing 10 informants consisting of managers, employee, and three members of KSPPS MPS and BMT Berkah. This interview was conducted during the working hours of the two sharia micro institutions. The results of this study indicate that from the aspect of reliability, assurance, tangible, empathy, and responsiveness, KSPPS MPS has fulfilled these five aspects. BMT Berkah still does not fulfill these five aspects, especially in terms of reliability and tangibles